Terrorism awareness: understanding the threat and how you can protect yourself - Deatherage, Robert Henry (CRC Press, 2023)
"Terrorism Awareness: Understanding the Threat and How You Can Protect Yourself provides readers a foundational understanding of the threats that face us every day. The goal is to introduce readers to different tactics and techniques used by terrorists - both international and domestic - to better understand personal protection concepts and, if necessary, take actions to make themselves "hard targets" that terrorist organizations will want to avoid. This includes providing a background on understanding how terrorists operate, and, more specifically, how to recognize the pre-incident indicators associated with terrorist operations"--